Reactor type impacts thermosonication inactivation kinetics of Lacticaseibacillus casei in postbiotic orange beverage - Cristiano Silva do Nascimento; Filipa Vinagre Marques Silva; Sueli Rodrigues (Innovative Food Science & Emerging Technologies, 2026)

Dietary supplementation with algae-based ingredients modulates antioxidant defenses and immune response in sea urchin Paracentrotus lividus following a Vibrio parahaemolyticus challenge - Ana Filipa Rodrigues; S. Lourenço; A.S. Gomes; M. Vaz; H. Cardoso; A.P. Violante; T. Baptista (Animal Feed Science and Technology, 2026)

Second primary cancers among females with a first primary cervical, uterine and ovarian cancer: a population-based study in North Portugal - Elisabete Gonçalves; Filipa Fontes; Jéssica Rocha Rodrigues; Rita Calisto; Maria José Bento; Nuno Lunet; Samantha Morais (Cancer Causes & Control, 2026)

Inclusion of microalga Dunaliella salina in the diet of laying hens: effects on egg quality and sensory traits - Obete Madacussengua; Cátia Falcão Martins; Ana Beatriz Rodrigues Tavares; Daniela Filipa Pires Carvalho; Ana Rita Mendes; Tiago Guerra; António Pagarete; Suzana Ferreira-Dias; Miguel Pedro Mourato; José António Mestre Prates; André Martinho de Almeida; Madalena Lordelo (Algal Research, 2026)

Benthic scavenger assemblages along a depth gradient: megafauna–macrofauna divergence - Diego Carreira-Flores; Filipa Rodrigues; Pedro T. Gomes; Marcos Rubal (Marine Environmental Research, 2026)

Diel activity guild drives different mammal responses to fragmentation and degradation in the Amazon deforestation arc - Luan G. A. Goebel; Ana Filipa Palmeirim; Juliano A. Bogoni; Gabriela Rodrigues Longo; Ana Catarina Araújo-Fernandes; Eder Correa Fermiano; Manoel dos Santos-Filho (Biodiversity and Conservation, 2026)
Fragmentation and degradation have profound effects on species’ habitat use and activity patterns. According to their diel activity guild, species may respond differently to environmental change, with diurnal species expected to be more vulnerable to these changes. Here, we test this hypothesis by investigating how fragmentation, and degradation modulate the habitat use and overlap in diel activity of contrasting mammal diel activity guilds in the Amazonian arc of deforestation. We used data from camera-traps (2,970 trap-days) across 30 forest fragments (from 8 to 435 ha) and three continuous forest sites. Considering diurnal and nocturnal mammals separately, we examine (1) the effects of fragmentation, and degradation on the habitat use and (2) the overlap in their diel activity across the different forest sizes. Habitat use by diurnal mammals increased with forest size, but not that of nocturnal species. In general, diurnal mammals anticipate their peak activity from 00:00 h to 6:00 h into smaller fragments (

In vivo evaluation of the anti-inflammatory efficacy of liposomes loaded with Echinacea purpurea roots extracts - Sara F. Vieira; Diana Fonseca-Rodrigues; Daniel Mendanha; Vânia I. B. Castro; Ricardo A. Pires; Rui L. Reis; Filipa Pinto-Ribeiro; Helena Ferreira; Nuno M. Neves (Drug Delivery and Translational Research, 2026)
WHO ranked chronic inflammatory diseases as the most significant cause of death. The current therapeutic approach is the constant administration of clinically available anti-inflammatory drugs; however, this strategy presents severe side effects. New entities derived from plants have shown their potential for developing safe and effective therapies. Particularly, Echinacea purpurea extracts have demonstrated strong anti-inflammatory properties. Therefore, dichloromethanolic extracts of E. purpurea roots (DE-R), rich in alkylamides, were used to produce an anti-inflammatory formulation. To increase therapeutic efficacy, DE-R were loaded into liposomes (LPs), which were also engineered to actively target M1 macrophages via surface functionalization with folic acid (FLPs). The developed formulations were homogeneous, with a mean particle size of ≈114 nm. The liposomes were cytocompatible at all tested concentrations and strongly reduced IL-6 production in LPS-stimulated macrophages. As expected, FLPs + DE-R were 6.3 times better than LPs + DE-R, and 9.7 times greater than free DE-R. The anti-inflammatory activity of free DE-R and DE-R-loaded FLPs was assessed in an experimental rat model of inflammation. A single intra-articular injection of the FLPs + DE-R promoted a significant reduction of edema, inflammatory pain, and immune cell infiltration, particularly of CD68 + macrophages, as well as IL-6 expression. This formulation reduced synovial inflammation more efficiently than free DE-R. We also demonstrated that the developed formulation was safe, as no welfare changes or harmful toxicity to major organs were observed. Therefore, E. purpurea roots extracts loaded in liposomes can be used as a natural, innovative, and powerful new formulation to treat chronic inflammatory diseases. Graphical Abstract

Nutrient deprivation stimulates soluble extracellular polymeric substances: physiological and biochemical responses in the cyanobacterium Cyanocohniella rudolphia - Filipa Rodrigues; Ivana Mendonça; Marisa Faria; Karine Mougin; Juan Luis Gómez Pinchetti; Artur Ferreira; Nereida Cordeiro (Algal Research, 2026)

Why marine gammarids belong to the future portfolio of aquafeed ingredients - Ricardo Calado; Marta Carvalho; Luísa Marques; Daniela P. Rodrigues; João P. Sousa; Felisa Rey; Maria Rosário Domingues; Joana Filipa Fernandes; Ruben X. G. Silva; Diana Madeira; Arne M. Malzahn; Óscar Monroig; et al. (Frontiers in Marine Science, 2025)
The sustainable supply of n-3 long-chain polyunsaturated fatty acids ( n -3 LC-PUFA) remains a major challenge for global aquaculture. Although plant oils, microalgae, genetically modified crops, insects, krill, and fish by-products have been explored as alternative sources, none currently provides a stand-alone solution for meeting the growing demand of n -3 LC-PUFA in aquafeeds’ production. Here, we present marine gammarids as a potential complementary source of these fatty acids. Our Perspective article focuses on the nutritional attributes of marine gammarids, including their naturally high levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and considers their biological traits that support aquaculture practicality. We also examine the potential of marine gammarids for circular bioeconomy applications through trophic upgrading of low-value side streams. While evidence from feeding trials is limited, preliminary data suggest marine gammarids may maintain their high EPA and DHA content even when fed on low-quality diets. Critical research priorities include developing scalable production systems, optimising feed formulations, evaluating performance across key aquaculture species, and assessing ecological and operational feasibility. This Perspective also highlights the potential of marine gammarids to contribute to a diversified and resilient aquafeed portfolio. Although they are unlikely to replace fish meal or fish oil entirely, marine gammarids may serve as a strategic complementary ingredient.

Soluble extracellular polymeric substances and microplastics: Exposure-response and circular reuse for removal - Filipa Rodrigues; Ivana Mendonça; Marisa Faria; Ricardo Gomes; Juan L. Gómez Pinchetti; Artur Ferreira; Nereida Cordeiro (Chemosphere, 2025)

Evaluating the efficacy of topical application of Genista tridentata (L.) (Fabaceae) leaf extract on wound healing in experimental diabetes - Inês Martins Laranjeira; Beatriz Gonçalves; Diana Rodrigues-Fonseca; Alberto C. P. Dias; Filipa Pinto-Ribeiro (Phytochemistry Letters, 2025)

Article Title: Impact of Dysphagia on Quality of Life in Machado-Joseph Disease - Joana Paz Mota; Inês Tello Rodrigues; Ana Filipa Ferreira; Ana Rosa Vieira Melo; Paula Pires; Pedro Lopes; João Vasconcelos; Mafalda Raposo; Manuela Lima (The Cerebellum, 2025)

Unraveling the nutraceutical potential of Salicornia ramosissima by-product – impact of gastrointestinal digestion and intestinal permeability on in vitro bioactivity - Diana Pinto; Inês Santos; Filipa Teixeira; Stefania Sut; Mónica Vieira; Miguel Salazar; Cristina Delerue-Matos; Stefano Dall'Acqua; Francisca Rodrigues (Food Chemistry, 2025)

Phytochemical diversity and biological activities of Hypericum japonicum and Hypericum sampsonii: potential for natural product-based food applications - Paula Barciela; Daniele B. Rodrigues; Ana Perez-Vazquez; Tayse F.F. da Silveira; Tânia C.S.P. Pires; Filipa Mandim; Maria Carpena; Carla Pereira; Isabel C.F.R. Ferreira; Lillian Barros; Miguel A. Prieto (Food Chemistry, 2025)

Valorization of natural resources - development of a functional plant-based beverage - Filipa A. Fernandes; Custódio Roriz; Ricardo C. Calhelha; Paula Rodrigues; Tânia C.S.P. Pires; Miguel A. Prieto; Isabel C.F.R. Ferreira; Lillian Barros; Sandrina A. Heleno (Food Chemistry, 2025)

Multi-faceted decline of vertebrate diversity in an endemism zone of the Brazilian Amazon - Luan Gabriel Araujo Goebel; Juliano A. Bogoni; Gabriela Rodrigues Longo; Ana Filipa Palmeirim; Eder Correa Fermiano; Dionei José da Silva; Áurea Regina Alves Ignácio; Manoel dos Santos-Filho (Journal for Nature Conservation, 2025)

Patterns and Drivers of Taxonomic and Functional Change in Large Oceanic Island Bird Assemblages - Filipa C. Soares; Ricardo F. de Lima; Ana S. L. Rodrigues; Pedro Cardoso; Thomas J. Matthews; Jorge M. Palmeirim (Global Ecology and Biogeography, 2024)
Aim We map global patterns of taxonomic and functional change between past (pre‐human impacts) and present (after anthropogenic extinctions and introductions) in large oceanic island bird assemblages and investigate if these patterns can be explained by island characteristics and anthropogenic factors. Location Sixty‐four oceanic islands (>100 km 2 ). Time Period Late Holocene. Major Taxa Studied Terrestrial and freshwater bird species. Methods We compiled information on extinct, extant native and introduced bird species for all islands and used a probabilistic hypervolume approach to build a multi‐dimensional trait space and calculate several functional diversity metrics before and after extinctions and introductions. We identified which islands are global hotspots of human‐induced transformation by mapping multiple facets of biotic change and investigated intrinsic island characteristics and anthropogenic factors as drivers for these observed patterns. Results The Hawaiian and Mascarene islands stand out as hotspots of taxonomic and functional change, but all islands changed taxonomically and functionally, mostly gaining species but losing functional richness. Taxonomic and functional changes vary across islands but are often consistent within the same archipelago. Island isolation and surface can explain some of the observed variations, but anthropogenic factors, namely human occupation, also shaped both taxonomic and functional changes. Islands with higher human pressure, as well as larger islands with high elevation ranges, tended to have greater losses in functional richness. Main Conclusions Most biodiversity change assessments are still largely based exclusively on taxonomic diversity, which is particularly worrying in the case of oceanic islands given that the magnitude of functional diversity change is often considerably larger. We call for comprehensive assessments of changes in both taxonomic and functional diversity across oceanic islands in order to better understand the drivers of these changes and, in turn, predict future trends.

Enhancing tomato plants' tolerance to combined heat and salt stress – The role of arbuscular mycorrhizae and biochar - Bruno Sousa; Cristiano Soares; Filipa Sousa; Maria Martins; Pedro Mateus; Francisca Rodrigues; Manuel Azenha; José Moutinho-Pereira; Teresa Lino-Neto; Fernanda Fidalgo (Science of The Total Environment, 2024)

Novel cold and thermally pasteurized cardoon-enriched functional smoothie formulations: A zero-waste manufacturing approach - Filipa Mandim; Spyridon A. Petropoulos; Carlos A. Pinto; Sandrina A. Heleno; Paula Rodrigues; Maria Inês Dias; Jorge A. Saraiva; Celestino Santos-Buelga; Isabel C.F.R. Ferreira; Lillian Barros; José Pinela (Food Chemistry, 2024)

Effect of solid-state fermentation of Brewer's spent grain on digestibility and digestive function of european seabass (Dicentrarchus labrax) juveniles - Tássia Estevão-Rodrigues; Helena Fernandes; Sara Moutinho; Diogo Filipe; Filipa Fontinha; Rui Magalhães; Ana Couto; Marta Ferreira; Margarida Gamboa; Carolina Castro; Isabel Belo; José Salgado; et al. (Animal Feed Science and Technology, 2024)

Understanding the Atlantic influence on climate and vegetation dynamics in western Iberia over the last 2000 years - Ricardo N. Santos; Teresa Rodrigues; Filipa Naughton; Enno Schefuß; Dulce Oliveira; João Moreno; Pedro M. Raposeiro; Graciela Gil-Romera; Alistair Morgan; Manel Leira; Sandra D. Gomes; S. Nemiah Ladd; et al. (Quaternary Science Reviews, 2024)

Ultrasound-assisted extraction of bioactive compounds from goji berries: Optimization, bioactivity, and intestinal permeability assessment - Filipa Teixeira; Ana Margarida Silva; Stefania Sut; Stefano Dall'Acqua; Oscar L. Ramos; Alessandra B. Ribeiro; Ricardo Ferraz; Cristina Delerue-Matos; Francisca Rodrigues (Food Research International, 2024)

Efficacy of bacterial cellulose hydrogel in microfiber removal from contaminated waters: A sustainable approach to wastewater treatment - Filipa Rodrigues; Marisa Faria; Ivana Mendonça; Edward Sousa; Artur Ferreira; Nereida Cordeiro (Science of The Total Environment, 2024)

Microalgal-based industry vs. microplastic pollution: Current knowledge and future perspectives - Ivana Mendonça; Marisa Faria; Filipa Rodrigues; Nereida Cordeiro (Science of The Total Environment, 2024)

Anthropogenic debris ingestion in a tropical seabird community: Insights from taxonomy and foraging distribution - D.M. Matos; J.A. Ramos; Filipa Bessa; Vítor Silva; Isabel Rodrigues; Stefan Antunes; I. dos Santos; João Coentro; A.L.C. Brandão; L.A.E. Batista de Carvalho; M.P.M. Marques; Sara Santos; et al. (Science of The Total Environment, 2023)

Comparative neurotoxicity of dietary methylmercury and waterborne inorganic mercury in fish: Evidence of optic tectum vulnerability through morphometric and histopathological assessments - Patrícia S. Carvalho; Diana Fonseca-Rodrigues; Mário Pacheco; Armando Almeida; Filipa Pinto-Ribeiro; Patrícia Pereira (Aquatic Toxicology, 2023)

Later prehistoric tin mining in the Ervedosa mine (Vinhais, Portugal): evidence and context - Emmanuelle Meunier; Filipa Dias; João Fonte; Alexandre Lima; Alexandra Rodrigues; Carlo Bottaini; Rui J. C. Silva; João P. Veiga; Manuel F. C. Pereira; Elin Figueiredo (Archaeological and Anthropological Sciences, 2023)

Combined effects of bird extinctions and introductions in oceanic islands: Decreased functional diversity despite increased species richness - Filipa C. Soares; Ricardo F. de Lima; Jorge M. Palmeirim; Pedro Cardoso; Ana S. L. Rodrigues (Global Ecology and Biogeography, 2022)
Aim We analyse the consequences of species extinctions and introductions on the functional diversity and composition of island bird assemblages. Specifically, we ask if introduced species have compensated the functional loss resulting from species extinctions. Location Seventy‐four oceanic islands (> 100 km 2 ) in the Atlantic, Pacific and Indian Oceans. Time period Late Holocene. Major taxa studied Terrestrial and freshwater bird species. Methods We compiled a species list per island (extinct and extant, native and introduced), and then compiled traits per species. We used single‐trait analyses to assess the effects of past species extinctions and introductions on functional composition. Then, we used probabilistic hypervolumes in trait space to calculate functional richness and evenness of original versus present avifaunas of each island (and net change), and to estimate how functionally unique are extinct and introduced species on each island. Results The net effects of extinctions and introductions were: an increase in average species richness per island (alpha diversity), yet a decline in diversity across all islands (gamma diversity); an average increase in the prevalence of most functional traits, yet an average decline in functional richness and evenness, associated with the fact that extinct species were functionally more unique (when compared to extant natives) than introduced species. Main conclusions Introduced species are on average offsetting (and even surpassing) the losses of extinct species per island in terms of species richness, and they are increasing the prevalence of most functional traits. However, they are not compensating for the loss of functional richness due to extinctions. Current island bird assemblages are becoming functionally poorer, having lost unique species and being composed of functionally more redundant species. This is likely to have cascading repercussions on the functioning of island ecosystems. We highlight that taxonomic and functional biodiversity should be assessed simultaneously to understand the global impacts of human activities.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Retina and Brain Display Early and Differential Molecular and Cellular Changes in the 3xTg-AD Mouse Model of Alzheimer’s Disease - Ana Catarina Rodrigues-Neves; Rafael Carecho; Sónia Catarina Correia; Cristina Carvalho; Elisa Julião Campos; Filipa Isabel Baptista; Paula Isabel Moreira; António Francisco Ambrósio (Molecular Neurobiology, 2021)

Fifteen years of a nationwide culture collection of Neisseria gonorrhoeae antimicrobial resistance in Portugal - Miguel Pinto; João Carlos Rodrigues; Rui Matias; Ivone Água-Doce; Dora Cordeiro; Cristina Correia; João Paulo Gomes; Maria José Borrego; Filipa Alegria; Ana Jacinta Piedade; Maria Beatriz Tomaz; Cristina Toscano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Modelling structural performance and risk for enhanced building resilience and reliability - Maria João Falcão Silva; Nuno Marques de Almeida; Filipa Salvado; Hugo Rodrigues (Innovative Infrastructure Solutions, 2020)

Year-Long Rhinovirus Infection is Influenced by Atmospheric Conditions, Outdoor Air Virus Presence, and Immune System-Related Genetic Polymorphisms - Ana Filipa Rodrigues; Ana Mafalda Santos; Ana Maria Ferreira; Roberta Marino; Maria Esmeralda Barreira; José Manuel Cabeda (Food and Environmental Virology, 2019)

The Retina as a Window or Mirror of the Brain Changes Detected in Alzheimer’s Disease: Critical Aspects to Unravel - Samuel Chiquita; Ana C. Rodrigues-Neves; Filipa I. Baptista; Rafael Carecho; Paula I. Moreira; Miguel Castelo-Branco; António F. Ambrósio (Molecular Neurobiology, 2019)

Unravelling the antitumoral potential of novel bis(thiosemicarbazonato) Zn(II) complexes: structural and cellular studies - Elisa Palma; Hugo M. Botelho; Goreti Ribeiro Morais; Inês Rodrigues; Isabel Cordeiro Santos; Maria Paula Cabral Campello; Paula Raposinho; Ana Belchior; Susana Sousa Gomes; Maria Fátima Araújo; Isabel Correia; Nadia Ribeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2019)

Health status-associated microbiota fingerprints within the oral cavity of cetaceans - Pedro Soares-Castro; Helena Araújo-Rodrigues; Filipa Godoy-Vitorino; Marisa Ferreira; Pablo Covelo; Alfredo López; José Vingada; Catarina Eira; Pedro Santos (Frontiers in Marine Science, 2019)

Unraveling the forcings controlling the vegetation and climate of the best orbital analogues for the present interglacial in SW Europe - Dulce Oliveira; Stéphanie Desprat; Qiuzhen Yin; Filipa Naughton; Ricardo Trigo; Teresa Rodrigues; Fátima Abrantes; Maria Fernanda Sánchez Goñi (Climate Dynamics, 2018)

Tauroursodeoxycholic Acid Enhances Mitochondrial Biogenesis, Neural Stem Cell Pool, and Early Neurogenesis in Adult Rats - Rita Soares; Filipa F. Ribeiro; Sara Xapelli; Tânia Genebra; Maria F. Ribeiro; Ana M. Sebastião; Cecília M. P. Rodrigues; Susana Solá (Molecular Neurobiology, 2017)

A case of multiple gastrointestinal stromal tumors caused by a germline KIT gene mutation (p.Leu576Pro) - Rita Vale Rodrigues; Filipa Santos; João Pereira da Silva; Inês Francisco; Isabel Claro; Cristina Albuquerque; Maria Manuel Lemos; Manuel Limbert; António Dias Pereira (Familial Cancer, 2017)

Water exchanges between a multi-inlet lagoon and the ocean: the role of forcing mechanisms - João Pedro Farinha Fabião; Marta Filipa Gomes Rodrigues; André Bustorff Fortunato; José Manuel Quintela de Brito Jacob; Alexandra Maria Francisco Cravo (Ocean Dynamics, 2016)